2018
DOI: 10.1111/arcm.12445
|View full text |Cite
|
Sign up to set email alerts
|

A Provenance Study of Early Bronze Age Artefacts Found in Asturias (Spain) by Means of Metal Impurities and Lead, Copper and Antimony Isotopic Compositions

Abstract: We describe here the first combined isotopic and impurities study on 27 copper artefacts found in the north-west of Spain. This study follows previous studies on the lead isotopic composition of copper ores in three local mines that were exploited during the Bronze Age. The levels of impurities found were clearly different from ingots and axes, with ingots having much higher levels of impurities. It was not possible to differentiate the origin of the artefacts only by the impurities present. On the other hand,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…These two ingots also showed high 207/206 Pb isotope ratio (0.8075 and 0.8254, respectively), which indicated a less radiogenic Pb source. For these two ingots, a positive identification of the raw material used was not possible, 17 while the rest of the samples showed a highly radiogenic Pb isotope composition compatible with the ranges shown by the La Profunda mine (Fig. S1†).…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…These two ingots also showed high 207/206 Pb isotope ratio (0.8075 and 0.8254, respectively), which indicated a less radiogenic Pb source. For these two ingots, a positive identification of the raw material used was not possible, 17 while the rest of the samples showed a highly radiogenic Pb isotope composition compatible with the ranges shown by the La Profunda mine (Fig. S1†).…”
Section: Resultsmentioning
confidence: 91%
“…Reguera-Galán et al 17 published analytical data on 27 copper-based archaeological artefacts found in Asturias (Spain) including data on Cu and Pb isotopic compositions and metal impurities. These 27 samples correspond to 4 different finding locations: The Asiego hoard, containing 14 arsenical copper axes (11 were measured), The Gamonedo hoard, containing 13 arsenical copper ingots and 1 axe (all were measured), a small sword from Corao and an axe from Gueraño.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent study, we analyzed 27 arsenical copper samples (ingots, axes and swords) relating to the Copper or Early Bronze Ages found in Asturias (Spain) and kept in the Archaeological Museum in Oviedo. 113 The results are shown in Fig. 18 (red points) compared to ranges of lead isotope ratios from different copper and lead mines published for the Iberian Peninsula.…”
Section: Applications Of Isotopic Measurementsmentioning
confidence: 99%